Sistem Pakar Diagnosa Mastoiditis Menggunakan Metode VCIRS Dan Naive Bayes - Arifin Khosim Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Mastoiditis is a disease in the form of infection on the back of the human ear, commonly known as the mastoid bone, which generally affects babies aged 6 to 13 months. Mastoiditis can destroy the spine of the human ear and cause hearing loss which can lead to death if not treated in time. This causes parents to first bring their baby to consult a mastoiditis specialist with the aim of obtaining information on the diagnosis of the disease experienced by their baby. The problem that often occurs when parents consult a specialist is the inefficient time to consult a specialist due to limited time and a large queue of patients, so that specialist doctors cannot always serve all patients who come for consultation. In overcoming the problems with the diagnosis of mastoiditis described above, the authors assess that a diagnostic aid based on information technology is needed in the form of an expert system with an effort to provide mastoiditis diagnosis information. Therefore in this study, designing an expert system for diagnosing mastoiditis by applying the variable centered intelligent rule system (VCIRS) method and the naïve Bayes method. This research is expected to provide positive benefits to an expert and also to people who are generally not familiar with the specifics of mastoiditis which is commonly referred to as mastoid